2017
DOI: 10.5812/zjrms.9621
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Cholecystitis and Presence of Helicobacter pylori in the Gallbladder

Abstract: Background: As there is an established relationship between Helicobacter pylori infection and gastric and duodenal ulcers, there might also be a relationship between this infection and other pathologies of gastrointestinal system. Objectives: Thus in this study we decided to investigate the relationship between H. pylori infection and cholecystitis. Methods: In this case-control study, patients were divided into two groups: case group with cholecystitis or cholelithiasis and controls with normal gallbladder. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…A total of 84 studied patients with mean age of 45.19±1.78, 27 were male (32.1%) and 57 were female (67.9%). 23 Findings of the present study were comparable with the other studies. In present study all the patients had abdomen pain and the duration of pain was one to two months in 25.71% and 11.43% had pain for six months.…”
Section: Discussionsupporting
confidence: 92%
“…A total of 84 studied patients with mean age of 45.19±1.78, 27 were male (32.1%) and 57 were female (67.9%). 23 Findings of the present study were comparable with the other studies. In present study all the patients had abdomen pain and the duration of pain was one to two months in 25.71% and 11.43% had pain for six months.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, similar results have been suggested in Japan, China, Saudi Arabia and Pakistan populations (9)(10)(11)(12). In many studies, the presence of HP in the GB was determined and its correlation with cholecystitis and cholelithiasis was shown (12)(13)(14). In our study, the correlation between the presence of cholelithiasis and HP was clearly seen.…”
Section: Discussionsupporting
confidence: 65%
“…16 Similarly in another study, similar results were found. 26 It is still not known how these bacteria find their way into the gall bladder, but most probable theory is that it travels from stomach to duodenum and through sphincter of Odi enters the biliary system and resides in gall bladder.…”
Section: Discussionmentioning
confidence: 99%